Suspicion and Love - Chrulew, Matthew (QLD University, 2013)
Recent philosophy has witnessed a number of prominent and ambivalent encounters with Christianity. Alongside the retrievals of Paul and political theology, thinkers such as Žižek and Negri argue that in our era of imperial sovereignty and advanced global capitalism, the most appropriate politics is one of love. These attempts to reinvigorate progressive materialism are often characterised as a break with the relativist tendencies of French philosophy, moving from the negativity and disconnection of postmodern suspicion to a new, constructive politics of creativity and fraternity. Deconstructive critiques have insisted on the exclusions necessary to any such politics of love. Foucault’s genealogy of Christianity—specifically, of the emergence from pastoral power of modern governmentality and biopolitics—sketches a further significant dimension of love’s suffocating history and contemporary risks